Towards (re)generative agriculture : an analysis of farms and gardens on Gotland - Ekroth, Filippa (SLU/Department of Molecular Sciences, 2021)
The challenges of adapting farming in response to climate change, degraded soils, depleted natural resources and an increasing population have created new agricultural concepts with focus on an environmentally long-term sustainable way of producing food. One possible solution presented is regenerative agriculture, an alternative form of food production that focus on building and re-forming resilient ecological systems supported by ecosystem processes. Regenerative agriculture works with various agricultural practices and management techniques and focus on the entire ecosystems to be able to establish a selfsustained well functional system. Techniques and practises used within the concept also contributes to building carbon in the soil, which leads to less impact on the climate. - However, the concept lacks a formalized definition and critical voices have been raised regarding its presumed positive impact on soil health, biodiversity, and carbon sequestration. This study thus aims to investigates farmers and gardeners currently practise regenerative agriculture on Gotland, Sweden’s largest island, to enabling future studies. A mixed method was used to enabling both collection of data in terms of management practises and techniques through a questionnaire and investigating thoughts and ideas about the concept with semi-structured interviews. The results illustrated regenerative agriculture as a flexible concept both in terms of practises and techniques used on the farm and gardens and as well the ideas and thoughts expressed.